Analytical method development and validation for simultaneous estimation of seven markers in polyherbal formulation JKC by using RP-HPLC - Lakshminarayana Misro; Thirupataiah Boini; Rahul Maurya; Thulasi Radhakrishnan; K. S. Rohith; Vijay Kumar; Preeti Sharma; Arjun Singh; Ravindra Singh; Naryanam Srikanth; Rabinarayan Acharya (SpringerOpen, 2024)
Abstract Background The RP-HPLC method has been established to simultaneous estimation of seven markers in polyherbal formulation JKC using the C18 (25 × 0.46 cm, i.d,5 µm) column. The mobile phase consisted of methanol: water (80:20) at a flow rate of 1.0 mL/min and observed retention time at 2 to 11 min with sharp points. The marker compounds viz. Andrographolide (AG), Piperine (PP), Picroside-I (P-I), Picroside-II (P-II), α-Cyprone (AC), 6-Shogaol (6S), and 6-Gingerol (6G) were quantified in JKC formulations by HPLC method. Detection was performed at the wavelength (λ) of 229 nm for AG, 343 nm for PP, 279 nm for P-I, 264 nm for P-II, 254 nm for AC, and 280 nm for both 6S and 6G by HPLC-PDA detector. Results The marker compounds in JKC formulations were observed in different retention times (Rt) i.e. AG at 3.060 ± 0.01 min, PP at 5.460 ± 0.03 min, P-I at 2.789 ± 0.02 min, P-II at 2.553 ± 0.03 min, AC at 10.951 ± 0.02 min, 6S at 6.302 ± 0.03 min, and 6G at 4.111 ± 0.02 min respectively. The proposed method was validated with acceptable linearity (r2 0.9995-0.9999), precision, robustness, ruggedness, and accuracy (RSD < 2%) under optimum conditions. The limit of detection and quantification of bioactive markers were as: AG (1.386; 4.200 ppm), PP (2.033; 6.161 ppm), P-I (2.822; 8.553 ppm), P-II (2.538; 7.691 ppm), AC (0.269; 0.815 ppm), 6G (0.158; 0.480 ppm), 6S (0.188; 0.569 ppm). The amount (mg/g) of bioactive markers detected and estimated in plants and formulation were as: AG (41.282 ± 0.48; 10.06 ± 0.18), PP (53.81 ± 0.25, 13.82 ± 0.37 in PN, PL; 4.27 ± 0.07), P-I (15.97 ± 0.01; 0.48 ± 0.003), P-II (63.24 ± 0.35; 2.31 ± 0.006), AC (0.42 ± 0.01; 0.36 ± 0.006), 6G (0.71 ± 0.03; 0.16 ± 0.001), and 6S (2.64 ± 0.09; 0.12 ± 0.004) respectively. Method was found to be rugged and robust. The results found for all the validation parameters were within the limits according to ICH guidelines. Conclusion The proposed method is fast, precise, economic, and specific and used for the simultaneously quantifiable analysis of seven major bioactive markers in the ingredients (herbs) and the JKC formulations.